1998
DOI: 10.1523/jneurosci.18-18-07394.1998
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Serotonin-1A Autoreceptors in the Midbrain of Suicide Victims with Major Depression—Postmortem Evidence for Decreased Serotonin Activity

Abstract: It has been hypothesized that a deficit in serotonin may be a crucial determinant in the pathophysiology of major depression. Serotonin-1A receptors are located on serotonin cell bodies in the midbrain dorsal raphe (DR) nucleus, and the activation of these receptors inhibits the firing of serotonin neurons and diminishes the release of this neurotransmitter in the prefrontal cortex. Repeated treatment with some antidepressant medications desensitizes serotonin-1A receptors in the rat midbrain. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
243
3
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(280 citation statements)
references
References 45 publications
25
243
3
7
Order By: Relevance
“…Work by Sargent et al (2000) included both medication free and subjects on antidepressant medication. Contrary to the data from these studies, postmortem work by Stockmeier et al (1998) indicated elevated rather than depressed binding of [ 3 H]8-OH-DPAT in the midbrain of suicide victims with major depression.…”
Section: Introductioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Work by Sargent et al (2000) included both medication free and subjects on antidepressant medication. Contrary to the data from these studies, postmortem work by Stockmeier et al (1998) indicated elevated rather than depressed binding of [ 3 H]8-OH-DPAT in the midbrain of suicide victims with major depression.…”
Section: Introductioncontrasting
confidence: 90%
“…Indeed, Stockmeier et al (1998) observed elevated autoreceptor number in the brains of suicide victims with major depression. Two in vivo studies of 5-HT 1A function in mid-life depression also contradicted the Stockmeier et al report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have confirmed our finding of higher TPH immunoreactivity in a second cohort of suicides and controls using immunoautoradiography (Boldrini et al, 2005). Further evidence of disordered function in DRN neurons of suicide subjects includes altered 5-HT 1A autoreceptor binding (Arango et al, 2001;Stockmeier et al, 1998), and both less serotonin transporter binding and expression (Arango et al, 2001). The combination of postmortem studies reporting low serotonin/5-HIAA midbrain levels in suicide, and in vivo studies reporting low CSF 5-HIAA in suicide attempters (Placidi et al, 2000), combined with postmortem findings of greater DRN TPH-IR neuron density, more TPH protein, and fewer transporter sites, suggests upregulation of biosynthetic capacity and putative transporter internalization in response to less serotonin.…”
Section: Introductionsupporting
confidence: 82%
“…serve as auto-or heteroreceptors, and control neurotransmitter release (Schlicker and Göthert, 1998;Starke, 1981). There is evidence that the density of some of these GPCR proteins, such as a 2 -adrenoceptors and 5-HT receptors, is altered in the brains of suicide victims and in the platelets of depressed patients (Callado et al, 1998;De Paermentier et al, 1997;García-Sevilla et al, 1986, 1999González et al, 1994;Meana et al, 1992;Meana and García-Sevilla, 1987;Mendelson, 2000;Ordway et al, 1994;Pandey et al, 1995;Sargent et al, 2000;Stockmeier et al, 1998). These alterations have been correlated with impaired neurotransmitter release that results from a 2 -adrenoceptor supersensitivity and/or serotonin receptor dysfunction.…”
Section: Introductionmentioning
confidence: 99%